Financial performance and survival of multinational corporations in China - Pan, Yigang; Chi, Peter S. K. (Strategic Management Journal, 1999)
This study investigates the impact of entry timing, mode of entry, market focus, and location advantages on the financial performance and survival of multinational corporations (MNCs) in China. Three major results were found. First, MNCs that entered China in an earlier year had a higher level of profit than those that entered in a later year. Second, equity joint ventures (EJVs) had a higher profit level than cooperative operations or wholly foreign-owned subsidiaries. Third, MNCs that utilized well the location advantages in China had a higher profit. We also found that EJVs were more likely to survive compared to cooperative operations, while wholly owned subsidiaries did not differ from EJVs. The findings are based on a 2-year study of about 1000 MNC operations in China. Copyright © 1999 John Wiley & Sons, Ltd.